2018
DOI: 10.4314/njbas.v25i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Gongola Basin Crust-Mantle Structural Analysis For Hydrocarbon Investigation Using Isostatic Residual Gravity Anomalies

Abstract: The isostatic residual gravity anomaly data of Gongola basin was computed by removing from the Bouguer gravity anomaly field, a regional gravity field calculated for compensation of masses of surface topography. The regional gravity field was computed using the Airy-Heiskanen isostacy model with compensation at the crust-mantle discontinuity. The free air, residual isostatic anomaly, density distribution maps and 2.5D gravity models were utilized in the definition of the basin's crust-mantle structures. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Seismic modeling was also done to determine the seismic velocity using the depth-normalized velocity iteration technique. Moreover, Epuh and Joshua [30] used gravity data to analyze the structural configuration in the Gongola basin for possible hydrocarbon exploration. The study revealed the presence of NE-SW and NW-SE structural trends.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic modeling was also done to determine the seismic velocity using the depth-normalized velocity iteration technique. Moreover, Epuh and Joshua [30] used gravity data to analyze the structural configuration in the Gongola basin for possible hydrocarbon exploration. The study revealed the presence of NE-SW and NW-SE structural trends.…”
Section: Introductionmentioning
confidence: 99%